Acute TREM2 inhibition depletes MAFB-high microglia and hinders remyelination - Jinchao Hou; Roberta Magliozzi; Yun Chen; Junjie Wu; John Wulf; Gregory Strout; Xiangming Fang; Marco Colonna (Proceedings of the National Academy of Sciences, 2025)
We investigated the role of Triggering Receptor Expressed on Myeloid cells 2 (TREM2) in myelin regeneration in the brain. TREM2 is a receptor that activates microglia, which are crucial for clearing myelin debris and promoting remyelination. Previous studies in a mouse model of demyelination induced by the copper-chelating agent Cuprizone (CPZ) have shown that stimulation of TREM2 with a monoclonal antibody reduces demyelination, while deleting the Trem2 gene in mice impairs remyelination. Here, we blocked TREM2 function acutely with an antibody during both the demyelination and remyelination phases of the CPZ model and analyzed the impact of the antibody treatment on myelination and gene expression in single cells. We found that blocking TREM2 depleted a distinct population of microglia with high expression of the transcription factor MAFB during remyelination. The loss of these MAFB-high microglia was linked to impaired generation of myelinating oligodendrocytes. Importantly, we identified MAFB + microglia in acute and acute-chronic brain lesions from individuals with multiple sclerosis (MS), but not in inactive lesions. We conclude that TREM2 is essential for maintaining a population of MAFB-high microglia that is associated with myelin repair. This finding has significant implications for understanding demyelinating diseases like MS and suggests that stimulating TREM2 could be a promising therapeutic approach for myelin repair.